Constant-Damage Yield Strength Spectra for RC Structures Using Modified Park-Ang Damage Model. Issue 6 (June 2015) - Jiang, Huanjun; Fu, Bo; Chen, Linzhi
In this study, constant-damage yield strength spectrum (CDYSS), which is defined as the yield strength demand of a single-degree-of-freedom (SDOF) system of varying natural vibration period with the target constant damage index and specified ductility capacity, is derived by averaging the nonlinear time-history analysis results of a SDOF system under different earthquake ground motions. A modified Park-Ang damage model proposed by the authors, eliminating its non-convergence problem both at upper and lower limits with higher precision and smaller scatter, is adopted to calculate the damage index of the SDOF system. In the construction of CDYSS, 641 sets of earthquake ground motion records are adopted and classified into 12 groups in line with Chinese code for seismic design of buildings. The yield strength demands of SDOF systems with given ductility capacity are obtained through trial and error method. Then, the mean CDYSS and the corresponding coefficient of variation for different group of site soil conditions are calculated. The effects of ductility capacity and local site soil conditions on CDYSS are discussed. Lastly, the empirical formulas of CDYSS are developed by multivariable nonlinear regression analysis and compared with actual CDYSS.